Prognostic value of the derived inflammatory marker SIRI in postmenopausal women with coronary artery disease - Yang, Pengli; Xue, Rui; Wei, Yuhang; Cao, Chenxi; Yu, Songcheng; Peng, Shanling; Zhang, Wenjing; Wang, Yunzhe; Zheng, Yingying; Liu, Gangqiong (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThe aim of this study was to explore the predictive value of the Systemic Inflammatory Response Index (SIRI) for the prognosis of older postmenopausal women with coronary artery disease (CAD).Patients and methodsThis retrospective cohort study included 617 postmenopausal female patients aged 50 years or older with a CAD diagnosis confirmed by coronary angiography seen at the First Affiliated Hospital of Zhengzhou University from January 2019 to December 2020. Patients were divided into three groups based on SIRI tertiles. Primary endpoints were all-cause mortality (ACM) and cardiac mortality (CM), and secondary endpoints were major adverse cardiovascular events (MACEs) and major adverse cardiovascular and cerebrovascular events (MACCEs).ResultsThe frequencies of all adverse outcomes were greater in the high level (third tertile) SIRI group than in the low level (first tertile) SIRI group. Multivariable regression analysis showed that compared to the low level SIRI group, the high level SIRI group had a 1.581-fold greater risk of ACM [hazard ratio (HR) = 2.581, 95% confidence interval (CI): 1.045–6.373, p = 0.040) and a 1.798-fold greater risk of CM (HR = 2.798, 95% CI: 0.972–8.060, p = 0.057). In addition, the risks of MACEs and MACCEs were 62.3% (HR = 1.623, 95% CI: 1.123–2.346, p = 0.01) and 55.8% (HR = 1.558, 95% CI: 1.100–2.207, p = 0.012) greater in the high level SIRI group compared with the low level SIRI group. Kaplan–Meier survival analyses confirmed that the high SIRI level was associated with increased risks of ACM (p = 0.001), CM (p = 0.005), MACEs (p = 0.003), and MACCEs (p = 0.005).ConclusionThis retrospective study demonstrates that the novel derived inflammatory index SIRI can effectively predict the risk of multiple adverse outcomes in postmenopausal women with CAD.